Solution for the homogenous equation
"y''-y=0"
"D^2-1=0; D=\\pm1"
"y_h=c_1e^x+c_2e^{-x}"
Using method of variations of parameters "c_1=c_1(x);c_2=c_2(x)" will give us the system
"\\begin{matrix}\n c_1'(x)e^x+c_2'(x)e^{-x}=0 \\\\\n c_1'(x)e^x-c_2'(x)e^{-x}=\\frac{2}{1+e^x}\n\\end{matrix}\\implies\n\\begin{matrix}\n c_1'(x)e^x=\\frac{1}{1+e^x}\n \\\\\n c_2'(x)e^{-x}=-\\frac{1}{1+e^x}\n\n\\end{matrix}"
"c_1(x)=\\int\\frac{e^{-x}}{1+e^x}dx=\\log(e^{-x}+1)-e^{-x}+c_1"
"c_2(x)=-\\int\\frac{e^{x}}{1+e^x}dx=-\\log(e^{x}+1)+c_2"
Therefore
"y=c_1e^x+c_2e^{-x}+(\\log(e^{-x}+1)-e^{-x})e^x-\\log(e^{x}+1)e^{-x}"
Comments
Leave a comment